2016
DOI: 10.1111/crj.12481
|View full text |Cite
|
Sign up to set email alerts
|

Electrical impedance tomography as possible guidance for individual positioning of patients with multiple lung injury

Abstract: Although therapeutic recommendations are available for gravitational influences of lung ventilation, they can be contradictory depending on the underlying lung disease. EIT has the potential to guide therapists in the positioning of patients according to their individual condition and disease, especially in case of multiple lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
(33 reference statements)
2
13
0
Order By: Relevance
“…It should be highlighted that EIT, is a non-invasive technique that does not generate radiation [56], [57], providing greater patient safety, although not yet widely studied as a possible method for monitoring joint injuries. This technique allows for the evaluation, diagnosis and detection of diseases such as: pneumothorax [58], brain disorders [59], [60], lung diseases in which both the effects of positive end-expiratory pressure are determined [61], [62], flow of gas in regions of the lungs [63], [64] and regional changes in the ventilation distribution [65], [66] based on the distribution of conductivity; making this technique a viable alternative in the study of joints [49], [51].…”
Section: Ingeniería Solidariamentioning
confidence: 99%
See 1 more Smart Citation
“…It should be highlighted that EIT, is a non-invasive technique that does not generate radiation [56], [57], providing greater patient safety, although not yet widely studied as a possible method for monitoring joint injuries. This technique allows for the evaluation, diagnosis and detection of diseases such as: pneumothorax [58], brain disorders [59], [60], lung diseases in which both the effects of positive end-expiratory pressure are determined [61], [62], flow of gas in regions of the lungs [63], [64] and regional changes in the ventilation distribution [65], [66] based on the distribution of conductivity; making this technique a viable alternative in the study of joints [49], [51].…”
Section: Ingeniería Solidariamentioning
confidence: 99%
“…As to EIT, there are commercial equipment such as the Pulmovista 500 [61], [64] and GOE MF II [68], [69], which have been developed and implemented for the diagnosis of different types of injuries with most related to pulmonary disorders, however, different electronic prototypes have been proposed using DSPs (Digital Signal Processor) [70], FPGAs (Field Programmable Gate Array) [71] and microcontrollers [72], [73]. These obtain tomographic images by taking into account the arrangement and geometry of the surface electrodes, the variation of the parameters of application and measurement of the signals and the image reconstruction algorithms [70], [71], [73].…”
Section: Ingeniería Solidariamentioning
confidence: 99%
“…Electrical impedance tomography (EIT) is a non‐invasive, highly dynamic tool that also provides regional functional information on lung ventilation. Although the high correlation between EIT and aeration of the lung during tidal breathing is well documented, EIT is still mainly used to provide information on lung aeration in intensive care settings to improve mechanical ventilation . However, preliminary studies have shown a similar correlation between EIT and aeration during forced expiration maneuvers when performing spirometry and during forced oscillation maneuvers .…”
Section: Introductionmentioning
confidence: 99%
“…Although the high correlation between EIT and aeration of the lung during tidal breathing is well documented, 3,4 EIT is still mainly used to provide information on lung aeration in intensive care settings to improve mechanical ventilation. [5][6][7][8] However, preliminary studies have shown a similar correlation between EIT and aeration during forced expiration maneuvers when performing spirometry [9][10][11][12][13][14][15] and during forced oscillation maneuvers. 16 This implies that EIT is also of potential value for pulmonologists, as it combines functional and regional information during pulmonary function testing.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical impedance tomography (EIT) is a non-intrusive, radiation-free, and portable biomedical imaging modality. There are many medical applications of EIT in the context of thorax imaging, such as lung ventilation monitoring [61,14,19,17,48,49,40], lung perfusion imaging [38,18], detection or evaluation of pneumonia [27,45], and assessment of pulmonary edema [56]. In EIT measurement, an array of electrodes are attached around a human chest.…”
mentioning
confidence: 99%